Évangélisation en Algérie : débats sur la liberté de culte - Karima Dirèche (L’Année du Maghreb)
The law regulating non-Muslim worship, enacted in February 2006, was implemented in 2008, with unprecedented severity in many cases of neo-evangelical conversion. Litigation of these cases has produced significant public debate on freedom of conscience and religion in Algerian society. The agitated debate is occurring within a framework for reform of state political institutions a general islamization of the political debate. The phenomenon of evangelization in Algeria raises other issues related to those of democratization (the debate that has occurred since the abrupt discontinuation of the electoral process of 1992) and authoritarian abuses of presidential power.